The Visible & Invisible in Thai Architecture Culture: The Problem of the Reduction & Discourses on Thai Architecture. - Kanitpun, Rachadaporn (Journal of Architectural/Planning Research and Studies (JARS), 2004)
The Visible and Invisible of Thai Architecture Culture concern with the fundamental problem of theory and concepts developed in contemporary Thai architectural culture. Traditional Thai architecture is characterized as a high gable with elevated terrace, a floor, and a courtyard [1], thus, with this perspective; to be genuine traditional ‘Thai’ architecture is to be constructed within this framework. This notion is, however, needed to be re-thought, and re-defined whether it is enough in the development of contemporary Thai architecture. Since, architecture is a dynamic organization, through built form, which brings together human behavior, sociology, economics, social hierarchical order, etc. [2]. Architecture, therefore, cannot be valued merely at its formal representation. It is, itself, life, unfortunately that along the history of architectural development, architecture is mainly perceived merely as a formal representation and leaves out what have generated those particular built forms. Through this; architecture becomes static which leads to nowhere but a museum where is preserved for spectacles, and separated from everyday life. This phenomena has happened in the development of contemporary Thai architecture in which built form is perceived as passive given seperatecy from social factors which lends its body. Thus, many of contemporary Thai architectures have lost its connection, not with the past but, with its time. This established notion is, also, found in most of the cultural studies in which culture is perceived as static and characterized as a symbol of the state or nation, which could not be changed. It becomes problematic since, as soon as culture is reduced to a merely representation, it looses not only its dynamism, but also its force and power. This paper is mainly concentrated on the construction of ‘Thai’ architecture. Attention is given to: - the social mechanism of the ‘Thais’ – the invisible, - how the invisible effects the construction of architecture, and its organization – the visible, and finally, - how architecture, and its organization, both the intangible (space, volume, proportion, scale etc.), and the tangible (form, wall, roof, floor, ornaments, material, etc.) functions in the construction of ‘Thainess.’ This paper is, however, not intended to criticize, nor to put the question of (Thai) Architecture to the conclusion, but rather it is intended to re-think, re-question, and re-define how architectural functions might be, by deferring a thought to the other fields of knowledge to which it might introduce different notions to the development of theory and concept in contemporary Thai architecture. Although the concentration is on the context of Thai, it is hoped to extend the discussion across the divided line between states and nations to the more broader sense which is what might be the development of theory and concept in architecture also, what architecture can do, to what extent do architectural academic and practices could bring about the value of its creation.